PENGARUH BRAND IMAGE PRODUK TERHADAP MINAT NASABAH ASURANSI SYARIAH ( Kasus Asuransi Syariah PT. Asuransi Takaful Keluarga Pekanbaru ) - M.Fauzan Azima; Lena Farida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Brand image to make belief - representing all important esensi to develop build a success business – do not only from in perpective all dealer but also from client. Brand have to can bear desire of client and than if that have been done/conducted to be expected by a client become interested to syariah insurance defance of all client of exist in generally will be more profit compared to by a client commutation. Expense to draw new client can fivefold bigger than at expense maintain client there is. Brand Image of PT. Asuransi Takaful Keluarga Pekanbaru have just good enough only felt less. According to Andi Mappiare interest is a mental device which consists of a mixture of feelings, hope, conviction, prejudice or another tendency that drive the individual to a particular choice.This research is done/conducted in PT. Asuransi Takaful Keluarga Pekanbaru, Grand Sudirman office complex D-2 Datuk Setia Maharaja/Parit Indah street Bukit Raya subdistrict. Pekanbaru. As for reason chosen Takaful Keluarga that to measure storey level of interest of client and the happening of percentage of descend sum up client. target of this Research is done/conducted to know influence of brand image to client interest.In this research is methodologies used by is quantitative and descriptive with program SPSS, where sample used by that is client and as source of information is party of Takaful Agency Director. To determine sampel use formula Slovin, method of sampling by accidental sampling. Technics of data collecting of through, observation and quesioner.From result analys data covering validity test, reabilitas, and linear regresi modestly, brand image to client interest. Each owning indicator which each other be interconnected and have an effect on positive to loyality in PT. Asuransi Takaful Keluarga Pekanbaru.Keyword: Brand Image and Client Loyality